The idea of metamorphosis in some English Renaissance writers - Chaudhuri, S; Chaudhuri, Supriya (1981)
﻿ This thesis explores the use made by Lyly, Spenser, Chapman and Marston of the idea of metamorphosis, with a brief epilogue on Jonson. The two preliminary chapters define certain important contexts for the theme of metamorphosis in this period. Chapter I briefly considers Ovid's use of the theme, the Pythagorean and Platonic theory of transmigration, and the allegorization of metamorphosis. Medieval commentaries on the Metamorphoses are examined, but it is argued that Renaissance attitudes to Ovid and to metamorphosis are significantly different, being uniquely sensitive to both the poetic and metaphysical aspects. Renaissance responses to Apuleius' Golden Ass are also examined. Chapter II studies other Renaissance contexts: in the philosophy of man, in magic, witchcraft and alchemy, and in the love-poetry of Petrarch and Ronsard. Neither Elizabethan lyric poetry nor the epyllion, however, make suggestive use of theltheme: it is explored more fully in larger structures or different poetic modes. The next four chapters deal with the English writers. Lyly's plays use the theme of metamorphosis in two contexts: love, and the adulatory myths of the court. Chapter IV considers the complex and varied uses of metamorphosis in Spenser's Faerie Queene. It examines the treatment of of myth, the concepts behind the Garden of Adonis, and transformation as related to the theme of mutability. Chapter V examines the idea of form, set against deformity or transformation, in Chapman's poetry: especially The Shadow of Night and Hero and Leander. Here the basic philosophic or metaphysical assumptions behind Renaissance views-of the myth of metamorphosis are defined. Chapter VI deals with the satiric use of transformation by Marston. His Metamorphosis of Pigmalions Image is analysed as parodying the common image of metamorphosis as an effect of love. The satires present a negative image of transformation caused by man's guilt and folly. The Epilogue, dealing with the negative image of transformation in Jonson's. plays and the positive one in the masques, concludes the study while suggesting further directions for exploration.